Identification of chlorite and serpentine in cosmetic or pharmaceutical talc. - Blount, A M (1983)
Chlorite is the most common accessory mineral group found in high purity talc ore used in cosmetic or pharmaceutical consumer talcum products. X-ray diffraction and wet chemical analytical data obtained on geologic samples representing commercial talc ore deposits of high purity and on processed samples representing talc found in consumer talcum products indicate that clinochlore and penninite are the two chlorite minerals most commonly found in all talc samples irrespective of origin or source, but sheridanite is also found in some samples representing talc deposits that are associated with serpentinite rocks. The chlorite minerals exhibit certain well-defined X-ray diffraction characteristics which differentiate them from each other as well as from those of serpentine minerals, including the hazardous chrysotile asbestos.